2013
DOI: 10.1111/jcpe.12097
|View full text |Cite
|
Sign up to set email alerts
|

Increased bone loss and amount of osteoclasts in kinin B1 receptor knockout mice

Abstract: Bdkrb1 participates in the pathogenesis of LIEP bone loss possibly through mechanisms that involve modulation of the TH 17 response, thereby demonstrating its role in the development of periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
(37 reference statements)
0
10
1
Order By: Relevance
“…However, WT C57/BL6 STZ-diabetic mice showed a marked reduction of collagen contents, with increased osteoblast apoptosis, with delayed healing regeneration, likely related to the up-regulation of B 1 R. detect any significant difference among the immunolabeling of RANK, RANKL, and OPG in non-diabetic and diabetic WT C57/ BL6 or B 1 RKO mice. GonS calves-Zillo et al, (2013) demonstrated an increased number of osteoclasts in animals lacking B 1 R by inducing in vitro differentiation of bone marrow cells with M-CSF and RANKL, contrasting to some degree with our data. In contrast, a recent study demonstrated that activation of B 1 R or B 2 R reduces osteoblast differentiation and stimulates osteoclasts, by mechanisms involving NF-kB-dependent gene regulation in vitro (Srivastava et al, 2014), reinforcing our results.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, WT C57/BL6 STZ-diabetic mice showed a marked reduction of collagen contents, with increased osteoblast apoptosis, with delayed healing regeneration, likely related to the up-regulation of B 1 R. detect any significant difference among the immunolabeling of RANK, RANKL, and OPG in non-diabetic and diabetic WT C57/ BL6 or B 1 RKO mice. GonS calves-Zillo et al, (2013) demonstrated an increased number of osteoclasts in animals lacking B 1 R by inducing in vitro differentiation of bone marrow cells with M-CSF and RANKL, contrasting to some degree with our data. In contrast, a recent study demonstrated that activation of B 1 R or B 2 R reduces osteoblast differentiation and stimulates osteoclasts, by mechanisms involving NF-kB-dependent gene regulation in vitro (Srivastava et al, 2014), reinforcing our results.…”
Section: Discussioncontrasting
confidence: 99%
“…This difference might be explained by: (i) the chemically‐induced model of type 1 diabetes adopted by us; (ii) the use of B 1 RKO mice instead of double B 1 R/B 2 R KO animals; and (iii) the evaluation methods for active bone remodeling, following the creation of a bone defect. It was shown that B 1 RKO mice displayed increased bone resorption in a model of ligature‐induced periodontitis; however, the authors did not assess the specific influence of diabetes, and there was an infectious component in their experimental approach (Gonçalves‐Zillo et al, ), which is not the case in this study.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…). Bradykinin is known as an inflammatory mediator and is also involved in bone metabolism . Thus, our results suggest that inflammatory signals in bone tissue are first received by osteoblasts, and are then transferred to sensory nerves.…”
Section: Discussionmentioning
confidence: 63%
“…Bradykinin normally exerts its effects through the activation of two seven transmembrane G protein-coupled receptors, named B1 and B2. It was reported that bradykinin can decrease the differentiation of osteoblasts with concomitant increase in osteoclast formation, consequently stimulating bone resorption and reduce BMD, [34][35][36] and that the lack of both B1R and B2R accelerated the loss of bone minerals.…”
Section: 4)mentioning
confidence: 99%